Comparison of the effects of Purslane cream and Lanolin for treatment of Breast Fissure on Lactation Self-efficacy: A Randomized Clinical Trial - Azin Niazi; Sedigheh Yousefzadeh; Hasan Rakhshandeh; Habibollah Esmaily (Majallāh-i zanān-i mamāʼī va nāzāʼī-i Īrān, 2018)
Introduction: Self-efficacy is an important motivating factor for success in lactation, so that increasing self-efficacy in the postpartum period leads to continued lactation. Performing lactation self-efficacy promotion interventions based on the sources of practical self-efficacy seems to be reasonable. Therefore, this study was performed with aim to compare the effect of Purslane cream and Lanolin for treatment of breast fissure on lactation self-efficacy. Methods: This double-blind randomized clinical trial was performed on 86 breastfeeding women with nipple fissure in Mashhad in 2016. The subjects were randomly assigned to two treatment groups of Purslane cream and Lanolin (n=43 in each group). Appropriate method of lactation and drug use were trained to both groups and they were asked to use treatment three times a day and up to one week. The score of nipple fissure was measured and recorded before the intervention, the third and eighth day after the intervention using the Store scale by the researcher. The tool of lactation self-efficacy was completed before the intervention and one day after treatment (8th day) through interview with the research units. Data were analyzed using SPSS software (version 22) and t-test, repeated measures variance analysis, Mann-Whitney, and Chi-square. PResults: According to the results of Mann-Whitney test, two groups were homogeneous in terms of mean score of fissure before the intervention, but there was significant difference between two groups on the third and eighth day (P <0.001). So that, recovery was faster observed in the Purslane creamgroup than Lanolin group. Self-efficacy score increased in both groups and this increase was significant in each group (P<0.001). However, this difference was not statistically significant when two groups were compared (P=0.434). Conclusion: Purslane cream in comparison with lanolin accelerated the recovery process of breast fissure and increased lactation self-efficacy score, although this difference was not significant.